The emotions of elderly people from the rural population - Dziechciaż, Małgorzata; Płaszewska-Żywko, Lucyna; Guty, Edyta (Polish Journal of Public Health, 2010)
Introduction. The aim of the study was to estimate the emotions of elderly people in the rural population. Material and methods. The study was carried out among 102 people (56 females and 46 males), 60-86 years old (average 73.18) in the Podkarpacie Province. The investigated group was intellectually active. The research was based on a self-made questionnaire, Hodkinson’s Abbreviated Mental Test Score, Yesavage’s Geriatric Depression Scale, Katz (ADL) Scale, Lawton Scale (IADL). Results. The majority of the investigated group (71.6%) were the people in the correct emotional state. It has been found out that the emotional condition deteriorates when people get older (p<0.001) and women assess their emotional condition to be worse than that of men (p<0.05). A large number of the examined had incomplete elementary education (54.9%) or full elementary education (18.6%). It was stated that poorly educated people were in a worse emotional condition when compared with people with higher education (p<0.01). The majority of the examined group (90.2%) were independent in performing activities of daily living (ADL), but also had a lot of problems with instrumental activities of daily living (IADL). There was also a correlation between lower efficiency in ADL and IADL and a worse emotional condition (p<0.01). The majority of the investigated (71.5%) had in their environment people who could help them anytime. It has been stated that women find it more difficult to get social support in comparison with men (p<0.01) and also people without social support were more predisposed to depression (p<0.001). Conclusions. Among the factors influencing the development of depression in elderly villagers were: obsolescence, female gender, poor education, lack of social support and worsening efficiency in ADL and IADL.